Paleogeodetic records of seismic and aseismic subduction from central Sumatran microatolls, Indonesia - Natawidjaja, Danny H. (2012)
We utilize coral microatolls in western Sumatra to document vertical deformation associated with subduction. Microatolls are very sensitive to fluctuations in sea level and thus act as natural tide gauges. They record not only the magnitude of vertical deformation associated with earthquakes (paleoseismic data), but also continuously track the long-term aseismic deformation that occurs during the intervals between earthquakes (paleogeodetic data). This paper focuses on the twentieth century paleogeodetic history of the equatorial region. Our coral paleogeodetic record of the 1935 event reveals a classical example of deformations produced by seismic rupture of a shallow subduction interface. The site closest to the trench rose 90 cm, whereas sites further east sank by as much as 35 cm. Our model reproduces these paleogeodetic data with a 2.3 m slip event on the interface 88 to 125 km from the trench axis. Our coral paleogeodetic data reveal slow submergence during the decades before and after the event in the areas of coseismic emergence. Likewise, interseismic emergence occurred before and after the 1935 event in areas of coseismic submergence. Among the interesting phenomenon we have discovered in the coral record is evidence of a large aseismic slip or “silent event” in 1962, 27 years after the 1935 event. Paleogeodetic deformation rates in the decades before, after, and between the 1935 and 1962 events have varied both temporally and spatially. During the 25 years following the 1935 event, submergence rates were dramatically greater than in prior decades. During the past four decades, however, rates have been lower than in the preceding decades, but are still higher than they were prior to 1935. These paleogeodetic records enable us to model the kinematics of the subduction interface throughout the twentieth century.